Diversity and participation in private apartment buildings: a review of the literature. (11th May 2018) - Liu, Edgar; Easthope, Hazel; Ho, Christina; Buckle, Caitlin
Abstract: Contemporary urban life has been shaped by two momentous shifts over the twentieth century: these shifts are increasing global mobility and increasing housing density, and both have required changes to personal approaches to dwelling. They have been pronounced in Australia, which has moved from an imperial‐colonial century to an Asian century in just over 100 years. Coupled with compact city policies in some regions, increased international migration has resulted in urban populations becoming more ethno‐culturally diverse, and encouraged urban residents to live in closer proximity to each other. Such trends are evident in the expansion of apartment living in cities. In the academic literature, each of these global shifts has been addressed separately, with much less attention being given to the two together. This oversight is especially the case in places where these changes are experienced most profoundly—private multi‐owned residential buildings that many and growing numbers of urban residents call home. The oversight is concerning because successful apartment living requires sustained participation and cooperation—how we dwell with each other matters. Without such forms of engagement and courtesies, apartment communities cannot run effectively or cohesively in terms of associational participation in management or of the everyday encounters of social life. Arguably, because global mobility is now so pronounced, engagement and civility require that people are respectfully observant of ethno‐diversity. Yet our review of the existing literature on multicultural encounters and participation in multi‐owned private apartment buildings suggests the need for more research on the intersections among global mobility, housing density, and apartment living. This paper begins to bridge this gap.